Mechanical Ventilation in Chronic Obstructive Pulmonary Disease Patients, Noninvasive vs. Invasive Method (Randomized Prospective Study) - Jurjević, Matija (Array, 2009)
Abstract: Acute respiratory failure due to chronic obstructive pulmonary disease (COPD) presents an increasing problem throughout the world. The aim of this study was to compare invasive and non-invasive mechanical ventilation (MV) for patients with COPD. A prospective, randomized trial was performed in a multidisciplinary intensive care unit for the period of 36 months and included 156 patients with COPD. MV procedure was performed using standard methods, and was applied as either invasive MV (IMV) or noninvasive MV (NIMV). Patients were randomized in two groups for application of MV using closed, nontransparent envelops. Comparison was made based on patient characteristics, objective parameters on admission and 1h, 4h, 24h, and 48h after admission and based on treatment outcome. We have confirmed that NIMV method is superior to IMV for patients with COPD. MV duration NIMV:IMV was 94:172 hours, p<0.001, time spent in Intensive Care Unit 120:223 hours, p<0.001. Ventilator associated pneumonia 5(6%):29(37%), p<0.001. The advantage of NIMV in COPD patients, especially in the early stages was confirmed